Infrared- and white-light retinal sensitivity in glaucomatous neuropathy - Łabuz, Grzegorz; Rayamajhi, Asu; Komar, Katarzyna; Khoramnia, Ramin; Auffarth, Gerd U. (Scientific reports, 2022)
Glaucoma causes irreversible neuropathy, which, untreated, may lead to blindness. In this case-control study, we measured two-photon infrared (IR) light sensitivity in glaucomatous eyes to propose a new method to quantify the visual loss. In total, 64 patients were recruited with an equal distribution between glaucoma and control groups. Retinal sensitivity to IR light was assessed using a two-photon excitation device. A fundus-driven microperimeter was used to measure retinal sensitivity to visible light. The retinal nerve fiber layer (RNFL) thickness was quantified automatically with optical coherence tomography. The IR sensitivity of glaucoma and control eyes differed significantly (P = .003): 9.8 (6.5 to 13.1) dB vs. 10.9 (8.2 to 13.0) dB. Although in the visible-light microperimetry, retinal sensitivity was decreased in glaucoma (17.0, range: 6.9 to 20.0 dB) compared to the controls (17.7, range: 11.6 to 20.0 dB), this difference did not reach the significance level. A significant thinning of the RNFL in the glaucoma group was observed (P < .001). IR sensitivity significantly correlated with the RNFL in three of the four assessed quadrants instead of only one in visible-light microperimetry. Although further research is needed, this proof-of-concept study suggests that IR-light sensitivity can be used to support the detection of glaucomatous neuropathy.